Sociālpedagoģiskā darbība pusaudžu agresivitātes mazināšanā Baltinavas kristīgajā speciālajā internātpamatskolā - Šakina, Renāte (Latvijas Universitāte, 2008)
Diplomdarba tēma ir „Sociālpedagoģiskā darbība pusaudžu agresivitātes mazināšanā Baltinavas Kristīgajā speciālajā internātpamatskolā”. Diplomdarbā tika izvirzīts mērķis - izpētīt pusaudžu agresivitātes izpausmes cēloņus un noskaidrot tās mazināšanas iespējas Baltinavas Kristīgajā speciālajā internātpamatskolā. Diplomdarbā tika veikti šādi uzdevumi: izpētīt literatūru par agresivitāti, raksturot pusaudžu agresivitātes cēloņus un izpausmes, pētīt pusaudžu vecumposma īpatnības, izpētīt situāciju Baltinavas Kristīgajā speciālajā internātpamatskolā pētāmās problēmas aspektā, izstrādāt un aprobēt izstrādāto programmu Baltinavas Kristīgajā speciālajā internātpamatskolā, veikt efektivitātes analīzi. Izmantotās metodes darbā - literatūras avotu analīze; sociālpedagoģiskā novērošana; anketēšana, rezultātu statistiska apstrāde. Diplomdarbs sastāv no – ievada, 6 nodaļām un 4 apakšnodaļām, nobeiguma, 46 literatūras avotu saraksta, 5 pielikumiem.

The topic of the diploma thesis is the “Social – educational activities to lower the teenager aggressiveness in the Baltinava Christian Special Boarding Elementary School”. The author has set the following goal for this diploma thesis: to examine the causes for the manifestation of the aggressiveness of the teenagers and to determine the possibilities of lowering this aggressiveness in the Baltinava Christian Special Boarding Elementary School. The following tasks were performed in this diploma thesis: to examine the literature on the aggressiveness, to characterize the causes and manifestations of the teenager aggressiveness, to explore the peculiarities of the teenager life stage, to examine the situation in the Baltinava Christian Special Boarding Elementary School in the aspect of the problem of the research, to produce and approbate the elaborated program with the Baltinava Christian Special Boarding Elementary School and to carry out the analysis of the effectiveness. The methods used in the thesis are the analysis of the literary sources, the social – educational observation, polling and the statistical processing of the results. The diploma thesis consists of the introduction, 6 chapters and 4 subchapters, the conclusion, 46 the list of the literary sources and 5 appendices.
Social pedagogical work for decreasing adolescents' aggresiveness at Baltinava Christian Specialized boarding school
Keywords: Pedagoģija